Android application and the improvement of academic performance of Basic Physics students - Rojas Mejía, Jhohan Mauricio; Casaliglla Ger, Darwin Fabricio (SATHIRI, 2025)
Learning Physics in the first semesters of university usually brings difficulties for students. Factors such as: lack of motivation, complexity of physical concepts and lack of effective training resources make learning a confusing process that is difficult to assimilate in its entirety. The use of educational material in Android applications has helped in different areas of study, however, the accessibility of applications in the area of Physics does not help the student in their learning to improve their academic performance. Based on this, the study aims to contribute with the use of an Android application that allows improving the performance of students in the subject of Physics. To find the needs of the students in the subject of Physics, information was collected through the use of surveys, in this way important parameters were established that determine the form and content of the Android application. The development of the application was carried out through a free-to-use platform, and it was shared with a group of students to evaluate performance when performing exercises and tasks using the supporting content provided by the application, which is made up of: text, images and calculation tools. When working with the application, students rated the practicality of the material as a help to understand and apply difficult content more easily.